Microbial Bioremediation of Fuel Oil Hydrocarbons in Marine Environment - Pavitran, Sapna; Jagtap, C.B.; Subramanian, S. Bala; Titus, Susan; Kumar, Pradeep; Deb, P.C. (Defence Science Journal, 2006)
Pollution in marine environment due to heavier petroleum products such as high-speed diesel is known to take from days to months for complete natural remediation owing to its low volatility. For the survival of marine flora and fauna, it is important to control pollution caused by such recalcitrant and xenobiotic substances. Several petroleum hydrocarbons found in nature are toxic and recalcitrant. Therefore, pollution due to high-speed diesel is a cause of concern. The natural dispersion of high-speed diesel, a slow process, is attributed to an overall combined effect of physico-chemical and biological processes which take months for complete dispersion. History of marine oil spill bioremediation indicates limited laboratory studies. But experiences from various oil spill management and field trials indicate important role of bioremediation, where, biodegradation of hydrocarbons through microbial mediators plays a major role in pollutant oil dispersion. These microbial mediators such as bioemulsifiers and fimbrae, help in emulsification, dispersion, allowing attachment of bacteria to oil layers, followed by substrate-specific enzymatic biodegradation in water.